-2x-7(8x-16)=4

Simple and best practice solution for -2x-7(8x-16)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-7(8x-16)=4 equation:


Simplifying
-2x + -7(8x + -16) = 4

Reorder the terms:
-2x + -7(-16 + 8x) = 4
-2x + (-16 * -7 + 8x * -7) = 4
-2x + (112 + -56x) = 4

Reorder the terms:
112 + -2x + -56x = 4

Combine like terms: -2x + -56x = -58x
112 + -58x = 4

Solving
112 + -58x = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-112' to each side of the equation.
112 + -112 + -58x = 4 + -112

Combine like terms: 112 + -112 = 0
0 + -58x = 4 + -112
-58x = 4 + -112

Combine like terms: 4 + -112 = -108
-58x = -108

Divide each side by '-58'.
x = 1.862068966

Simplifying
x = 1.862068966

See similar equations:

| 15=8-5(c+7) | | 18+y-1=16+y | | 4g=-16 | | N-6=50 | | 12n+2=-36 | | 2r-3=16+21 | | -.60(y-4)=-3 | | -7x-4(-8x-16)=-14 | | u+15=-13 | | x=.1x+5 | | 17x-7y=-5 | | X-3y+12=0 | | 2(2a+7)-7a=2(a+2) | | 27-9x+15y= | | 5(2x-12)=60x | | 5t+2(t+8)= | | 2(x-4)+8=3x-8+2x | | -5=4h-15 | | 2(x-4)+8=8x+2x | | 5-3(2x-1)=2x+4 | | 3x-(-x)+2y= | | 4(a-7)+8=2(a-4) | | -6p+4p=4(1+2p)-8(2p+5) | | 4x+5x=6x | | 0.9x-0.5(5-x)=6.6 | | X(3x)=486 | | 4x+7=-30 | | -7+8=3 | | 9x+4=2x+32 | | 0.015w-1.85=1.615 | | -4(2t+8)=-8 | | -2(-7n-8)-8n=6(n-6) |

Equations solver categories